Enhancing undergraduate EFL students’ research-related writing skills through a mini e-book chapter project - Lestari Setyowati; Sari Karmina; Elvira Rosyida MR; Shafie Asmaak Latisha (Universitas Islam Malang, 2026)
It is important for the university students to develop research-related academic writing skills as they need to prepare themselves to write a thesis proposal and other forms of academic writing communication. However, many still struggle to show comprehension and express basic research elements in writing, even after completing academic writing courses. Even though previous studies have shown Project-Based Learning (PjBL)’s effectiveness to enhance general writing performance and 21st-century skills, not much research in ELT higher education has focused on the use of PjBL for research-related writing in content courses. This gap suggests that students may not yet receive sufficient opportunities to practice research-related writing in meaningful and contextualized ways. To address this issue, the present study examined the effectiveness of a PjBL mini e-book chapter project in enhancing undergraduate EFL students’ research-related academic writing skills in a Designing Research in ELT course. A mixed-methods explanatory sequential design was employed involving 24 fourth-semester English education students at a public university in Malang. In addition to students’ reflections and interview responses, their learning gains were measured through pre- and post-tests. The findings suggest that the project had a meaningful impact on their writing performance. The mean scores increased from 69.69 to 79.74, and the paired-sample t-test indicates a significant improvement (p < .001) and has a large effect size (Cohen’s d = 1.02). Qualitative findings further confirmed improvements in research literacy, motivation, and 4Cs. These results highlight the potential of PjBL as an instructional innovation for strengthening research-related academic writing skills in similar EFL contexts.